2004
DOI: 10.1002/jctb.1143
|View full text |Cite
|
Sign up to set email alerts
|

Titration methodologies for monitoring of anaerobic digestion in developing countries—a review

Abstract: An increase in volatile fatty acids (VFA) concentration (or the proportional decrease in carbonate alkalinity concentration) is the first practical measurable indication that an anaerobic treatment system is in a state of stress. If the system is not rectified at this early stage, failure is likely. Current methods for VFA measurement include distillation, colorimetry, gas chromatography and various titration techniques. In terms of simplicity, speed and cost-effectiveness it is generally accepted that titrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(79 citation statements)
references
References 14 publications
2
73
0
Order By: Relevance
“…3a) during the same period. During this period, NH 3 -N, which is also known to act as a buffer against the acidic VFA effect (Lahav and Morgan 2004), also decreased slightly from 3 to 2.8 g/L (Fig. 2a).…”
Section: Effects Of Intermediate Vfa During Digestionmentioning
confidence: 92%
See 1 more Smart Citation
“…3a) during the same period. During this period, NH 3 -N, which is also known to act as a buffer against the acidic VFA effect (Lahav and Morgan 2004), also decreased slightly from 3 to 2.8 g/L (Fig. 2a).…”
Section: Effects Of Intermediate Vfa During Digestionmentioning
confidence: 92%
“…Reduction in pH during digestion may result to poor methanogenic activities, which may lead gradually to inhibition (Izumi et al 2010;Griffin et al 1998). For proper performance of methanogenic bacteria, it has been reported that the pH of the digestion medium should be within the range of 6.8 to 7.8 (Zeshan and Karthikeyan 2012;Lahav and Morgan 2004). Although there was more rapid pH drop during the digestion of F1, however, the pH was still within neutral bounds of 6.5 to 7.2 during the first 10 days of digestion before decreasing below pH 6.…”
Section: Assessment Of Other Parametersmentioning
confidence: 99%
“…the ability of a solution to neutralise acids, and can be expressed in different ways. The total alkalinity (TA) gives a measure of the combined effect of several different buffering systems [76] The partial alkalinity (PA) represents the buffering capacity of the carbonate system, and includes in addition the ammonium-ammonia system. The intermediate alkalinity (IA) is the difference between TA and PA and includes mainly the buffering capacity of the VFA [75,76].…”
Section: Ph Is An Important Parameter Influencing Methane Productionmentioning
confidence: 99%
“…The total alkalinity (TA) gives a measure of the combined effect of several different buffering systems [76] The partial alkalinity (PA) represents the buffering capacity of the carbonate system, and includes in addition the ammonium-ammonia system. The intermediate alkalinity (IA) is the difference between TA and PA and includes mainly the buffering capacity of the VFA [75,76]. The stability of the process can be evaluated by calculating the IA/PA ratio where a ratio of 0.3 or less indicates a stable process [75,77].…”
Section: Ph Is An Important Parameter Influencing Methane Productionmentioning
confidence: 99%
“…Dry matter (DM) and volatile matter (VM) content of substrates and inocula were measured according to Mayland [11] and Standard Methods [12]. Total alkalinity and total volatile fatty acids (TVFA) were measured by titration according to Lahav & Morgan [13]. 29.6±2.85 1947±63 4878±49 1856±270 * total alkalinity as mg-CaCO3 ** total volatile fatty acids as mg-CH3COOH 1) stabilized sludge from a swine farm biogas digester 2) mature digestate from a pilot reactor…”
Section: Substrates and Inoculamentioning
confidence: 99%